(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In India Tourism related MSMEs are liable to get the facilities like friendly banking services, easy finances, wide coverage of insurance, erosion of financial intermediaries, etc. This will help the tourism related MSMEs to flourish and prosper in the country. As of now, there are a number of facilities provided to new MSMEs but still there is a scope to facilitate the existing MSMEs in the country, like providing them with appropriate credit facilities, tax holidays, etc. so that they can directly contribute to the economic development of the country. This present study will evaluate the finance and credit related issues of MSMEs, especially in case of the tourism. This study is based on primary data and the researcher has used ANOVA test to verify the hypothesis.